Space for the Liminal - Belair-Gagnon, Valerie (2019)
This essay considers how social actors in news have come to shape the contours of news and journalism and what these changes may suggest for other industries. It looks more specifically at the question of who does journalism and news and what that may signal for power dependencies, status, and norms formation. It examines how authors who contributed to this thematic issue define who gets to decide what is news and journalism, what forms of power are exerted amongst groups, who gets to claim status, and how norms and epistemologies are formed. Ultimately, this essay illustrates how conformity to groups and organizations varies with the investments that these social actors have to core and more peripheral journalism and media groups.